Feasibility of working with a wholesale supplier to co-design and test acceptability of an intervention to promote smaller portions: an uncontrolled before-and-after study in British Fish & Chip shops. Issue 2 (6th February 2019) - Goffe, Louis; Hillier-Brown, Frances; Hildred, Natalie; Worsnop, Matthew; Adams, Jean; Araujo-Soares, Vera; Penn, Linda; Wrieden, Wendy; Summerbell, Carolyn D; Lake, Amelia A; White, Martin; Adamson, Ashley J
Abstract : Objectives: To explore the feasibility of working with a wholesale supplier to co-design and deliver, and to assess the acceptability of, an intervention to promote smaller portions in Fish & Chip shops. Design: Uncontrolled before-and-after study. Setting: Fish & Chip shops in northern England, 2016. Participants: Owners (n=11), a manager and customers (n=46) of Fish & Chip shops; and intervention deliverers (n=3). Intervention: Supplier-led, three-hour engagement event with shop owners and managers, highlighting the problem of excessive portion sizes and potential ways to reduce portion sizes; provision of box packaging to serve smaller portions; promotional posters and business incentives. Data collection: In-store observations and sales data collected at baseline and postintervention. Exit survey with customers. Semistructured interviews with owners/managers and intervention deliverers postintervention. Results: Twelve Fish & Chip shops were recruited. Observational data were collected from eight shops: at baseline, six shops did not promote the availability of smaller portion meals; at follow-up, all eight did and five displayed the promotional poster. Seven out of 12 shops provided sales data and all reported increased sales of smaller portion meals postintervention. Of 46 customers surveyed: 28% were unaware of the availability of smaller portion meals; 20% had bought smaller portion meals; and 46% of those who had not bought these meals were interested to try them in the future. Interviews revealed: owners/managers found the intervention acceptable but wanted a clearer definition of a smaller portion meal; the supplier valued the experience of intervention co-production and saw the intervention as being compatible with their responsibility to drive innovation. Conclusions: The co-design of the intervention with a supplier was feasible. The partnership facilitated the delivery of an intervention that was acceptable to owners and customers. Sales of smaller meal packaging suggest that promotion of such meals is viable and may be sustainable.